2010
DOI: 10.2225/vol13-issue4-fulltext-12
|View full text |Cite
|
Sign up to set email alerts
|

Rapid multiplication and in vitro production of leaf biomass in Kaempferia galanga through tissue culture

Abstract: An efficient protocol has been established for rapid multiplication and in vitro production of leaf biomass in Kaempferia galanga L, a rare medicinal plant. Different plant growth regulators like Benzyladenine (BA), Indoleacetic acid (IAA), Indolebutyric acid (IBA), Napthaleneacetic acid (NAA) and adenine sulphates (Ads) have been tried for induction of multiple shoots using lateral bud of rhizome as explants. The highest rate of shoot multiplication (11.5 ± 0.6) shoot/explant as well as leaf biomass productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Pre-sterilisation technique and sterilisation using mercury chloride significantly reduced contamination in this study ( Table 1 ). In support of our observation, mercuric chloride (HgCl 2 ) was also reported to be beneficial in reducing contamination in in vitro culture of other Kaempferia species ( Shirin et al 2000 ; Chirangini et al 2005 ; Parida et al 2010 ). Mahmoud and Al-Ani (2016) found that HgCl 2 mainly has bactericidal action and is a more effective sterilant with better decontamination percentages compared to sodium hypochlorite.…”
Section: Discussionsupporting
confidence: 71%
“…Pre-sterilisation technique and sterilisation using mercury chloride significantly reduced contamination in this study ( Table 1 ). In support of our observation, mercuric chloride (HgCl 2 ) was also reported to be beneficial in reducing contamination in in vitro culture of other Kaempferia species ( Shirin et al 2000 ; Chirangini et al 2005 ; Parida et al 2010 ). Mahmoud and Al-Ani (2016) found that HgCl 2 mainly has bactericidal action and is a more effective sterilant with better decontamination percentages compared to sodium hypochlorite.…”
Section: Discussionsupporting
confidence: 71%
“…Comparatively, a favorable effect of IAA over other auxins in the present study is in consonance with the report in A. calcarata [13] and Curcuma haritha [29]. The inefficiency of NAA and IBA along with BAP in the present system was similar to the recent observations in Kaempferia galanga [30].…”
Section: Resultssupporting
confidence: 93%
“…Shoot multiplication occurred by axillary bud proliferation maintains genetic stability in tissue cultures than by adventi tious bud formation (Balachandran et al 1990; Downloaded by [Laurentian University] at 19:07 09 October 2014 Shenoy & Vasil 1992;Joshi & Dhawan 2007). Molecular marker-based analysis of miropropagated and conventional grown K. galanga was reported by Mohanty et al (2010) and Parida et al (2010). ISSR markers are universal, quick to use, and easy to apply; they have the reproducibility of SSR markers due to the longer length of their primers (Bornet & Branchard 2001).…”
Section: Assessment Of Genetic Stabilitymentioning
confidence: 99%